2020
DOI: 10.1002/ange.201910297
|View full text |Cite
|
Sign up to set email alerts
|

13.34 % Efficiency Non‐Fullerene All‐Small‐Molecule Organic Solar Cells Enabled by Modulating the Crystallinity of Donors via a Fluorination Strategy

Abstract: Non-fullerene all-small-molecule organic solar cells (NFSM-OSCs) have shown potential as OSCs,o wing to their high purity,easy synthesis and good reproducibility.However, challenges in the modulation of phase separation morphology have limited their development. Herein, two novel small molecular donors,B TEC-1F and BTEC-2F,d erived from the small molecule DCAO3TBDTT,are synthesized. Using Y6 as the acceptor,d evices based on non-fluorinated DCAO3TBDTT showed an open circuit voltage (V oc )o f 0.804 Vand ap owe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Compared with the convenient interpenetration structure in the polymer systems, suitable size of nanofibrous domain in all small molecular systems is prerequisite which could supply favorable exciton separation and charge transport pathway. [ 22,24 ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with the convenient interpenetration structure in the polymer systems, suitable size of nanofibrous domain in all small molecular systems is prerequisite which could supply favorable exciton separation and charge transport pathway. [ 22,24 ]…”
Section: Resultsmentioning
confidence: 99%
“…[ 16–21 ] However, small molecular donors normally possessed stronger crystallinity but a weaker ability to form interpenetrating network in all‐small‐molecule organic solar cells (ASM‐OSCs). [ 22–24 ] Lack of efficient charge transport channel would restrict the exciton diffusion, charge separation, and charge transport, which could interpret why the fill factor (FF) of ASM‐OSCs was not as high as that of polymer solar cells. [ 25–27 ] Therefore, tuning the morphology of the active layer is one of the most critical factors which need to be considered for the performance improvement for ASM‐OSCs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These unsatisfactory results mainly originate from the limited materials system and the hardly controlled morphology. While thanks to the innovation of NFAs as well as SMDs, we have witnessed impressive results with PCEs around 9% to 12% since 2017 35‐40 . Recently, Hou et al demonstrated an encouraging PCE of 15.3% (certified 15.1%) 41 for the binary devices.…”
Section: Introductionmentioning
confidence: 89%
“…Due to the advantages of simple preparation and good film quality, spin-coating has become the conventional method for preparing OSCs. [27][28][29][30][31] Unfortunately, in the process of preparing the active layer film by spin-coating, the active layer solution will be thrown out of the substrate, causing material waste. At the same time, as the effective area increases, the thickness of active layer film will be uneven because of the different forces at the substrate center and edges.…”
mentioning
confidence: 99%